2006
DOI: 10.3989/egeol.0662131
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The localities of Arroyo del Val and La Barranca, placed in the same geological levels and separated by no more than 100 m, are located within the fossiliferous area of Arroyo del Val, near the villages of Villafeliche and Daroca (province of Zaragoza, Spain) (fig. 1). This zone is known since 1980 for its remarkable richness in mammal fossil sites, aging from the Aragonian to the early Vallesian. The two mentioned localities yielded a nice sample of fossil carnivores, but it has been never deeply studied. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…4, figs. 4–6 2006 Amphicyon giganteus Peigné, Salesa, Antón and Morales ( 2006b ), p. 365, pl. 2, figs.…”
Section: Systematic Palaeontologymentioning
confidence: 99%
See 1 more Smart Citation
“…4, figs. 4–6 2006 Amphicyon giganteus Peigné, Salesa, Antón and Morales ( 2006b ), p. 365, pl. 2, figs.…”
Section: Systematic Palaeontologymentioning
confidence: 99%
“…No upper dentition behind the P2 was preserved. These teeth, especially the upper carnassial and molars, are often used in identifying Amphicyonidae and separating Amphicyon giganteus from A. major (Gürbüz 1974 ; Peigné et al 2006b ; Jiangzuo et al 2019 ). Another characteristic often used in separating the taxa is size, but both A. giganteus and A. major display significant variation in size, which can largely be explained by sexual dimorphism, as males are larger than females in both species (Viranta 1996 ).…”
Section: Comparisonmentioning
confidence: 99%
“…In Antunes and Ginsburg (1977). 1965, Ginsburg andAntunes 1968, Ginsburg 1999, Peigné et al 2006. Some of the large species from the early Miocene have been classified in other amphicyonid genera such as Ysengrinia and Crassidia (Heizmann and Kordikova 2000) and even in Pseudocyon (Ginsburg 1967, 1999, Heizmann and Kordikova 2000.…”
Section: Megamphicyon Carnutense (Antunes Et Ginsburg 1977)mentioning
confidence: 99%
“…Some of the older forms from the early Miocene (MN 2-3) have received different determinations, including Amphicyon giganteus carnutense anTunes et GinsburG 1977, Amphicyon giganteus laugnacensis GinsburG, 1989 and Amphicyon (Megamphicyon) lathanicus GinsburG, cHeneVal, JanVier, PouiT et sen, 2000 (see Ginsburg 2000bGinsburg , 2002. However, the type species, Megamphicyon giganteus (scHinz, 1825), would be reserved for the largest species with molars similar in size to those from the type locality of Averay (France), also found in some European localities of MN 4-6 age (Artenay, Baigneaux, La Romieu, Pont Levoy and Arroyo del Val among others), where molar sizes can greatly exceed that of Amphicyon major (Ginsburg 1989, 1999, Peigné et al 2006). However, there is a need for an indepth review of this group, a task that lies beyond the scope of the present research.…”
Section: Megamphicyon Carnutense (Antunes Et Ginsburg 1977)mentioning
confidence: 99%
“…Between three to nine species of Protictitherium are recognized in Europe and western Asia by different authors (Werdelin & Solounias 1991, 1996Ginsburg 1999;Turner et al 2008;Fraile 2016Fraile , 2018. The best records are from middle to late Miocene localities in several European countries, such as Greece (Bonis & Koufos 1991; Koufos 2011), Turkey (Schmidt-Kittler 1976;Andrews & Tobien 1977;Kaya et al 2005;Mayda et al 2015;Koufos et al 2018), Spain (Ginsburg et al 1981Peigné et al 2006;Fraile 2016Fraile , 2018 (1991) suggested that Tungurictis is a junior synonym of Protictitherium Kretzoi, 1938 and predicted that, when lower cheek teeth become available, the m1 entoconid should not be emphasized over the hypoconid and its talonid reduced relative to trigonid. Continued explorations in the Tunggur area in the last 25 years did eventually produce an associated partial skull and dentaries (IVPP V 13784) from the Tairum Nor locality in the lower part of the Tunggur Formation (Wang 2004), which largely confirmed Hunt & Solounias' prediction.…”
Section: Introductionmentioning
confidence: 99%